26=8+u

Simple and best practice solution for 26=8+u equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 26=8+u equation:


Simplifying
26 = 8 + u

Solving
26 = 8 + u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-1u' to each side of the equation.
26 + -1u = 8 + u + -1u

Combine like terms: u + -1u = 0
26 + -1u = 8 + 0
26 + -1u = 8

Add '-26' to each side of the equation.
26 + -26 + -1u = 8 + -26

Combine like terms: 26 + -26 = 0
0 + -1u = 8 + -26
-1u = 8 + -26

Combine like terms: 8 + -26 = -18
-1u = -18

Divide each side by '-1'.
u = 18

Simplifying
u = 18

See similar equations:

| -3f=18-f | | -6x^2-x-4=0 | | 53-7x=15+12x | | 0=x^2+2y^2+4y-2x+1 | | d-23d= | | 28=5x+3(2x+11) | | (2xh)+(2xh)+(h+h)=180 | | 16x+9=15x-4 | | (X+7)(3x+5)=0 | | 3(4x-3.2)=5x-9.6 | | 3(2-3x)=52 | | 2x-4+3x=7x-3 | | 70x+90=90 | | 7x-5=5x-6 | | x^2-6x=22 | | 6u-9+3(2u+3)=4(u+3) | | 4(x+1.78)=3x | | 8n+16=8 | | 200x-0.08=600x+0.52 | | 3x+7=-2x+27 | | 6-6x=6x-10x+10 | | 3.9x-73=2.4x+5 | | 8z-24=6+2z | | 5m-7=10+3m | | 6.2=8x+1.4 | | 6-6x=6x-10+10 | | 6n-2=1 | | -4(v-4)=-7+37 | | 2y-8+14=-6 | | 2t-7=-16+t | | 3+3u=6 | | -19=5(u-5)-8u |

Equations solver categories